2015
DOI: 10.1089/aid.2015.0089
|View full text |Cite
|
Sign up to set email alerts
|

HIV Transmission Patterns Among Immigrant Latinos Illuminated by the Integration of Phylogenetic and Migration Data

Abstract: Latinos represent a growing proportion of HIV cases in North Carolina (NC). Understanding how immigrants are involved in local HIV transmission is important to guide interventions. We used phylogenetics to characterize Latino involvement in local HIV transmission chains. Transmission clusters were identified from maximum-likelihood phylogenies constructed with HIV pol sequences from 177 Latinos and 1,496 non-Latinos receiving care in NC. Highly supported clusters involving one or more Latinos were characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Previous studies in the United States indicating that immigrant populations are more than likely infected with HIV after immigration have focused on specific populations, have been limited in their geographic scope, and have used methods other than transmission network analysis. 3,14,19,20,21, Our findings using national data corroborate and expand on findings from these smaller studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies in the United States indicating that immigrant populations are more than likely infected with HIV after immigration have focused on specific populations, have been limited in their geographic scope, and have used methods other than transmission network analysis. 3,14,19,20,21, Our findings using national data corroborate and expand on findings from these smaller studies.…”
Section: Discussionsupporting
confidence: 88%
“…13 Another study focusing on HIV transmission patterns among Hispanics/Latinos in North Carolina showed that foreign-born Hispanics/Latinos were more likely to be in clusters with other Hispanics/Latinos compared to U.S.-born Hispanics/Latinos. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Many of the articles analyzed explicitly problematize the role of immigration in local HIV dynamics (Dennis et al, 2015;González-Alba et al, 2011;2013;Lai et al, 2020), often refracting the general problematization of immigration through the rationale that molecular HIV surveillance is a useful public health tool in as much as it "estimate[s] the impact of immigration on national and local HIV dynamics" (González-Alba et al, 2011), or how certain so-called risk groups with immigrant backgrounds contribute to "the import of other HIV strains" (Lai et al, 2020). The articles often position molecular HIV surveillance as a solution to the "problem" of immigration and HIV, often framing this position through a recourse to "targeted HIV preventive measures" (Dennis et al, 2015;González-Alba et al, 2011), such as linkage to care and HIV testing within risk networks.…”
Section: Content Analysis Andmentioning
confidence: 99%
“…Moreover, the article concludes that South American transgender women often "do not practice safe sex" and that these women "could have a bridging role in the spread of HIV among both Italian MSM and heterosexuals" (Lai et al, 2020). Other articles from both Spain and the USA echo this emphasis on the active role of immigrant MSM and transgender women (Dennis et al, 2015;González-Alba et al, 2011), with a sub-theme being a focus on whether they acquired HIV in their countries of origin or destination. These articles relate their focus to the transmission dynamics occurring in these immigrants' destination countries and to the role immigrants play in onward HIV transmission there (Dennis et al, 2015;Lai et al, 2020), thus alluding to immigrants' active role in local HIV dynamics.…”
Section: Content Analysis Andmentioning
confidence: 99%
“…Phylogenetic studies highlight the role of migration in bridging the HIV epidemic between North and South America 2 , and suggest that most Latinx immigrants acquire HIV after arrival to the US 3 . Economic, social, and political forces in the country of origin, during transit, and in the US often put migrants at risk of physical and emotional harm 4,5 .…”
Section: The Continuity Of Hiv Care Among Latinx Immigrantsmentioning
confidence: 99%